2022
DOI: 10.1002/brb3.2562
|View full text |Cite
|
Sign up to set email alerts
|

Suicide prevention in Bangladesh: The role of family

Abstract: Background: Suicide is a public health problem that gets little attention in Bangladesh especially in prevention aspects. Recent studies revealed that a significant portion of risk factors is closely related to family events. However, potential prevention strategies considering the family structure and involving family dynamics of Bangladesh have not been discussed. Objectives:We aim to highlight areas of family vulnerability and resilience when the threat of suicide is present, as well as the potential roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 58 publications
0
4
0
2
Order By: Relevance
“…We identified only three married people in our study, which raises the question of the possible role of an anomic marital status (single, divorced, widower) in making these individuals more vulnerable when confronting the consequences of the COVID-19 pandemic. We consider the literature data indicating that the family should play an important preventive role [ 48 ] to be correct (even though family tensions were surely to arise after the onset of the COVID-19 pandemic), but our findings show that these potential preventive measures would have less impact in a pandemic context.…”
Section: Discussionmentioning
confidence: 79%
“…We identified only three married people in our study, which raises the question of the possible role of an anomic marital status (single, divorced, widower) in making these individuals more vulnerable when confronting the consequences of the COVID-19 pandemic. We consider the literature data indicating that the family should play an important preventive role [ 48 ] to be correct (even though family tensions were surely to arise after the onset of the COVID-19 pandemic), but our findings show that these potential preventive measures would have less impact in a pandemic context.…”
Section: Discussionmentioning
confidence: 79%
“…Para isso, no contexto das políticas públicas recomenda-se abordar o tema de maneira não alarmista e não estigmatizante, conscientizando e estimulando a prevenção do suicídio, para contribuir para o enfrentamento deste problema de saúde pública (3) . Neste contexto, os formuladores de políticas e programas de saúde devem considerar o papel importante que a família pode desempenhar na prevenção e tratamento do risco de suicídio, inclusive com o apoio da mídia de massa, em promover o debate sobre o tema, destacando a responsabilidade e a influência da conexão familiar nesse cenário (20) . Rev Gaúcha Enferm.…”
Section: Comecei a Trabalhar Na Fábrica De Calçados Porque Via Que Co...unclassified
“…Diante disso, um estudo de Bangladesh (20) recomenda, enquanto estratégias de prevenção para o comportamento suicida, a promoção da resiliência familiar por meio da educação familiar sobre o comportamento suicida, os fatores de risco e de proteção nas situações identificadas, bem como realizar intervenções focadas na família para melhorar o funcionamento familiar, resolver problemas interpessoais, aumentar a integração familiar e o apoio social. Com isso, um estudo de revisão (25) revelou que aspectos e processos familiares podem servir de fatores de risco e de proteção para o suicídio, requerendo portanto intervenções psicossociais que mobilizam os recursos familiares nos diferentes situações relacionadas ao suicídio.…”
Section: Ya Eu Já Falei! Nós Não Nos Batemos Nos Damos Bem (Risos) El...unclassified
“…Thus, in the context of public policies, it is recommended that the topic be addressed in a non-alarming and non-stigmatizing way, raising awareness and encouraging people to prevent suicide, to contribute to the confrontation of this public health problem (3) . Thus, policy makers and health programs should consider the important role that can be played by the family in the prevention and treatment of suicide risk, and that can count on the support of the mass media in promoting the debate on the topic, highlighting the responsibility and the influence of family connection in this scenario (20) .…”
Section: Started Working At the Shoe Factory Because I Realized That ...mentioning
confidence: 99%
“…In this regard, a study from Bangladesh (20) recommends, as prevention strategies for suicidal behavior, the promotion of family resilience through family education on suicidal behavior, risk and protection factors in identified situations, as well as carry out family-focused interventions to improve family functioning, solve interpersonal problems, increase family integration and social support. A review study (25) revealed that family aspects and processes can serve as risk and protective factors for suicide, therefore requiring psychosocial interventions that mobilize family resources in different situations related to suicide.…”
Section: Ya I Already Told You! We Don't Hit Each Other We Get Along ...mentioning
confidence: 99%